ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL UNTUK MENCEGAH KREDIT MACET PEMBIAYAAN MUSYARAKAH MODAL KERJA YANG DIBERIKAN OLEH BANK - Syah Putra, Norman; Widarsono, Agus; Nasim, Arim (Jurnal ASET (Akuntansi Riset), 2013)
Abstract. The investigation is aimed at knowing the internal control system as one of the ways done to prevent bad debts/ bad credits of musyarakah financing, as the capital provided by the bank at BJB Syariah KCP Sukajadi. Besides, this study was also performed know the implementation of internal control system in that bank; whether or not it was done well by the department of Marketing Funding and Financing as the executor of that system itself. The method employed in this study was qualitative through phenomenology and case study. The data used in this study were the primary data taken from the results of in depth interview, participatory observation and the secondary data consist of several documents such as the audio recording of the interview between the researcher and the informant being interview and other related documents. The primary fountain of the data in this study were the head of BJB Syariah KCP Sukajadi, the operational manager, Marketing Funding and Financing department, Customer Service department, and Financing Support and Back Office Administration department. Meanwhile, the fountain of the secondary data was the related documents and the supporting literature. From the identification results of the results of the study and discussion done which referred to the five components of internal control system in COSO (Comitee of Sponsoring Organization of the Threadway Comission) namely 1) controlling environment, 2) the management of risk estimation, 3) controlling activities, 4) information and communication, and 5) supervising, it was concluded that the internal control system at BJB Syariah KCP Sukajadi was categorized week to minimize bad debts/ credits especially in musyarakah financing as the capital provided by the bank. Keywords: internal control system; bad debts/bad credits; capital musyarakah financingAbstrak. Investigasi ini bertujuan untuk mengetahui sistem pengendalian intern sebagai salah satu cara untuk mencegah kredit macet / kredit macet pembiayaan musyarakah, karena modal yang diberikan oleh bank BJB Syariah KCP Sukajadi. Selain itu, penelitian ini juga dilakukan untuk mengetahui implementasi sistem pengendalian intern di bank tersebut; apakah dikerjakan dengan baik oleh departemen Marketing Funding and Financing sebagai pelaksana sistem itu sendiri. Metode yang digunakan dalam penelitian ini adalah kualitatif melalui fenomenologi dan studi kasus. Data yang digunakan dalam penelitian ini adalah data primer yang diambil dari hasil wawancara mendalam, observasi partisipatif dan data sekunder terdiri dari beberapa dokumen seperti rekaman audio wawancara antara peneliti dan informan yang sedang wawancara dan dokumen terkait lainnya. Sumber data utama dalam penelitian ini adalah kepala BJB Syariah KCP Sukajadi, manajer operasional, departemen Pendanaan dan Pembiayaan Pemasaran, departemen Customer Service, dan Bagian Pendukung Pendukung dan Bagian Back Office. Sementara itu, air mancur data sekunder adalah dokumen terkait dan literatur pendukungnya. Dari hasil identifikasi hasil penelitian dan pembahasan yang dilakukan yang mengacu pada lima komponen sistem pengendalian intern di COSO (Comitee of Sponsoring Organization of the Threadway Comission) yaitu 1) lingkungan pengendali, 2) pengelolaan estimasi risiko, 3 ) kegiatan pengendalian, 4) informasi dan komunikasi, dan 5) pengawasan, disimpulkan bahwa sistem pengendalian intern BJB Syariah KCP Sukajadi dikategorikan berminggu-minggu untuk meminimalkan kredit macet / kredit khususnya pembiayaan musyarakah sebagai modal yang disediakan oleh bank.Kata kunci: sistem pengendalian internal; Â kredit macet; modal musyarakah pembiayaan